2010
DOI: 10.1016/j.stem.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Human Peripheral Blood Cells to Induced Pluripotent Stem Cells

Abstract: Direct reprogramming of human fibroblasts to induced pluripotent stem cells (iPS) has been achieved by ectopic expression of defined transcription factors. Derivation of human fibroblasts however is a time consuming process and requires punch biopsies or isolation of patient foreskin. Here we use a polycistronic vector encoding Oct4, Klf4, Sox2 and c-Myc to generate iPS cells from from frozen peripheral blood of several donors. Genomic DNA analyses indicated that iPS cells were derived from mature T cells as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
269
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(283 citation statements)
references
References 31 publications
2
269
0
4
Order By: Relevance
“…Because the AF cells we used in this study could be mixtures of different cell populations, we could not identify the origin of the iPS cells by cell type. Recently, it has been reported that blood cells may be a good source for generating iPS cells (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Because the AF cells we used in this study could be mixtures of different cell populations, we could not identify the origin of the iPS cells by cell type. Recently, it has been reported that blood cells may be a good source for generating iPS cells (37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have generated T cell-derived iPS cells, [5][6][7][8] but not much is known about differentiating these cells back into antigen-specific T cells.…”
Section: By Tracey Baas Senior Editormentioning
confidence: 99%
“…Blood sample collection and storage are among the routine procedures in hospitals and clinics. Therefore, significant efforts have been made to develop efficient and safe procedures for reprogramming various types of blood cells (Table 1) [10,11,[13][14][15][16][17][18][19][20][21]. Umbilical cord blood (UCB) cell banks provide another rich source for cells with diverse HLA types.…”
Section: Generation Of Patient-specific Ipscsmentioning
confidence: 99%
“…T cells, which are abundant in peripheral blood and amenable to ex vivo expansion after stimulation of T cell receptor (TCR) activation, were the first subtypes of lineage-committed human blood cells being reprogrammed [16][17][18]. Analyses of the TCR genomic loci had shown the evidence of V(D)J recombination in resultant iPSCs, demonstrating their T cell origin [16][17][18]24]. These studies also provided the most convincing evidence that terminally differentiated human cells can be reprogrammed into a pluripotent state.…”
Section: Generation Of Patient-specific Ipscsmentioning
confidence: 99%